Development of a framework for the investigation of speed, power, and kinematic patterns in para cross-country sit-skiing: A case study of an LW12 athlete - Baumgart, J. K.; Haugnes, P.; Bardal, L. M.; Østerås, S.; Kocbach, J.; Sandbakk, O. (Frontiers in Sports and Active Living, 2019)
Objective: To develop a framework for the investigation of speed, power, and kinematic patterns across varying terrain in cross-country (XC) sit-skiing, and to test this framework in a XC sit-skier of the LW12 class during high- (HIT) and low-intensity (LIT) endurance training.